Tracking mucosal innate immune responses to three influenza A virus strains in a highly translational pig model using nasopharyngeal swabs - Helena A Laybourn; Charlotte Kristensen; Anders G Pedersen; Louise Brogaard; Sophie George; Betina L Henriksen; Chrysillis H Polhaus; Ramona Trebbien; Lars E Larsen; Kerstin Skovgaard (Innate Immunity)
Background Four influenza pandemics have occurred during the past 100 years, and new variants of influenza viruses will continue to emerge. The nasal mucosa acts as the primary site of exposure to influenza A virus (IAV) infection, but viral recognition and host immune responses in the nasal mucosa are still poorly understood. Objectives This study aimed to evaluate the utility of non-invasive nasopharyngeal swabs for longitudinal monitoring of mucosal immune responses in pigs experimentally challenged with two swine-adapted and one human-adapted IAV. By tracking antiviral immune responses from disease onset to recovery, we sought to assess the feasibility of this method for capturing dynamic changes in viral load and host responses across different IAV strains. Methods Forty-two IAV-negative pigs were divided into four groups and housed separately for infection studies. Viral and host RNA from nasopharyngeal swabs was analyzed using microfluidic qPCR, while statistical analysis was performed with a Bayesian approach in R. Additionally, immunohistochemical staining was used to assess MUC5AC expression in the nasal mucosa of infected pigs. Results RNA was successfully isolated from nasopharyngeal swabs, enabling gene expression analysis to monitor innate immune responses to IAV infection. A classical innate antiviral immune response was demonstrated after the three virus infections including expression of pattern recognition receptors (PRRs), transcription factors, interferons (IFNs), interferon-stimulated genes (ISGs), cytokines, and chemokines. The kinetics and magnitude of immune responses varied between infections, with notable downregulation of mucins following infection with the Danish swine-adapted isolate. Further, the Danish isolate induced a fast but transient IFN-mediated response concurrent with high expression of cytokines and chemokines, while the other swine-adapted Mexican isolate induced a prolonged immune response of ISGs, cytokines, and chemokines. Conclusion This study highlights the significance of highly translational nasopharyngeal swabs as a non-invasive method for assessing mucosal antiviral immune responses. Utilizing microfluidic mRNA analysis, we gained valuable insights into antiviral mucosal responses across 216 swab samples collected from viral inoculation through recovery in three distinct influenza virus infections.